2015
DOI: 10.3390/molecules20022208
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Addiction Drug Ibogaine and the Heart: A Delicate Relation

Abstract: The plant indole alkaloid ibogaine has shown promising anti-addictive properties in animal studies. Ibogaine is also anti-addictive in humans as the drug alleviates drug craving and impedes relapse of drug use. Although not licensed as therapeutic drug and despite safety concerns, ibogaine is currently used as an anti-addiction medication in alternative medicine in dozens of clinics worldwide. In recent years, alarming reports of life-threatening complications and sudden death cases, temporally associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 71 publications
(192 reference statements)
4
100
0
Order By: Relevance
“…Unfortunately, we did not perform genotyping in our patient. Finally, both hypokalemia and hypomagnesemia may increase the risk of TdP [3]. Even though the disturbances were minimal in our patient, we cannot be certain it did not have an impact on the manifestation of cardiac arrhythmias.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Unfortunately, we did not perform genotyping in our patient. Finally, both hypokalemia and hypomagnesemia may increase the risk of TdP [3]. Even though the disturbances were minimal in our patient, we cannot be certain it did not have an impact on the manifestation of cardiac arrhythmias.…”
Section: Discussionmentioning
confidence: 66%
“…Although human studies on ibogaine are relatively scarce, recent literature has detailed the pharmacokinetic and pharmacodynamic profile of ibogaine. In the liver and gut wall, ibogaine is metabolized into biologically active noribogaine by mostly CYP2D6 and to a lesser extent by CYP2C9 and CYP 3A4 [2,3]. As a consequence, blood concentrations of ibogaine and noribogaine can be influenced by polymorphism in the CYP2D6 enzyme and co-ingestion of other medication metabolized by CYP2D6 may have clinical impact [4].…”
Section: Introductionmentioning
confidence: 99%
“…First, studies have suggested that ibogaine is effective in easing opioid withdrawal, as well as in reducing cravings (Brown 2013). Although the pharmacological bases of ibogaine’s anti-addictive properties are not fully understood, ibogaine and noribogaine (ibogaine’s main metabolite) simultaneous action on a diversity of neurotransmitter transporters and receptors provides a biological plausibility for its anti-addictive effects (Antonio et al 2013; Koenig & Hilber 2015). Second, ibogaine is usually administered in a single session, not requiring ongoing administration (Brown 2013), which can be a substantial advantantage for many individuals with OUD.…”
Section: Discussionmentioning
confidence: 99%
“…Ibogaine is an alkaloid found in the Tabernanthe iboga root bark, traditionally used in initiatory rituals in West Central Africa (Brown 2013; Koenig & Hilber 2015). Since the 1960s, anecdotal evidence has suggested its potential to treat addictions without the need for ongoing administration (Alper 2001; Brown 2013; Glick et al 1991; Maisonneuve, Keller & Glick 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation